Identification of Alkaloid Compounds from Cytotoxic Active Fraction in Peperomia pellucida - M Alvien Ghifari; Enny Fachriyah; Khairul Anam; Dian Nopitasari; Kautsar Elvira; Rama Esa Perdana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
Peperomia pellucida attracts a lot of interest due to its bioactivity and has been used in various folk medicine. In this report, n-hexane, dichloromethane, and ethyl acetate fraction of Peperomia pellucida extract were examined for its cytotoxic activity against Artemia salina larvae using the BSLT method. The ethyl acetate fraction showed higher cytotoxic activity than n-hexane and dichloromethane. The LC50 of ethyl acetate, n-hexane, and dichloromethane fractions was 39.665, 278.920, and 60.808 ppm, respectively. Mayer and Dragendorff tests give a positive result to the alkaloid constituent in ethyl acetate fraction. The alkaloids in Peperomia pellucida were extracted using ethyl acetate and further separated using chromatography techniques. Two alkaloid components were identified in ethyl acetate fraction from Peperomia pellucida as Piperine and Nigramide N by using LC-MS/MS.